Combination of AI and Human Expertise in Advancing Audio Forensic Investigation: AI Transcription and AI Sound Recognition in Legal Practice - Rota Ranavalonatina Ramahefarivo (Proceeding International Conference Restructuring and Transforming Law, 2025)
This study consists of evaluating the power of emerging AI that can be used in audio forensic investigation: these are AI Transcription and AI sound recognition. The combination of these AI Technologies with human expertise will offer a bright future by enhancing the investigation practices, especially audio forensic practice, in order to have better results in terms of efficiency, accuracy and reliability. This research will investigate these instruments effectiveness: Human expertise and AI combination; to give valuable insights that will help practitioners, scholars, and researchers in the field of audio forensic practice. With a legal pragmatic perspective, the study will be in the form of qualitative research, analyzing and reviewing related documents, AI articles, legal articles and concerned international regulations. The objective of this research consists of filling the gap of empirical studies, that assess Human-AI combination effectiveness, in audio forensic field. This empirical studies have not yet been done in previous literatures. The results and discussions highlight the strong power of innovation and AI technologies, such as AI Transcription and AI sound recognition, in accuracy and efficiency. But this AI integration still needs expert intervention, to ensure a fair and just outcomes in the audio forensic investigation, by bringing rigorous critical thinking, contextual analysis, subjective interpretation, emotion understanding and rational judgment. The results and discussions will end with a table, demonstrating the effectiveness of traditional methods, versus AI, versus combined methods. However, the conclusion part requires the Human-AI combination methods in audio forensic, to align with ISO legal standards.